Transcriptional Regulation of Telomerase Reverse Transcriptase (TERT) by MYC - Khattar, Ekta; Tergaonkar, Vinay (Frontiers in Cell and Developmental Biology, 2017)
Telomerase elongates telomeres and is crucial for maintaining genomic stability. While stem cells and cancer cells display high telomerase activity, normal somatic cells lack telomerase activity primarily due to transcriptional repression of telomerase reverse transcriptase (TERT), the catalytic component of telomerase. Transcription factor binding, chromatin status as well as epigenetic modifications at the TERT promoter regulates TERT transcription. Myc is an important transcriptional regulator of TERT that directly controls its expression by promoter binding and associating with other transcription factors. In this review, we discuss the current understanding of the molecular mechanisms behind regulation of TERT transcription by Myc. We also discuss future perspectives in investigating the regulation of Myc at TERT promoter during cancer development.